DUKUNGAN KELUARGA TENTANG PEMENUHAN ACTIVITY DAILY LIVING (ADL) PADA LANSIA DI KABUPATEN PARIGI MOUTONG - Diah Fitri Purwaningsih (Sekolah Tinggi Ilmu Kesehatan Indonesia Jaya Palu, 2023)
The results of observations and interviews with researchers on patients and nurses show that patients are less. Increasing the life expectancy of the elderly from year to year. This can lead to various health prob-lems and decreased productivity. Elderly is a process of growth and development that will be experienced by everyone. This process begins at conception and continues until death. This study aims to determine family support through emotional support, appreciation, instrumental and information on the fulfillment of Activity Daily Living (ADL) in the elderly in Parigi Moutong Regency. Family support research variables regarding the fulfillment of Activity Daily Living (ADL) in the elderly with this type of research using descriptive methods. The population in this study amounted to 75 elderly people. While the sample size in this study was 39 elderly people. The sampling method used a purposive sampling technique that used the Activity Daily Living (ADL) questionnaire and the analysis carried out on each variable from the results of the study was univariate analy-sis. The results of good emotional support family research were 20 people (51%). Most of the respondents who received Sufficient award support were 19 people (49%). Most of the respondents who received sufficient in-strumental support were 25 people (64%). Most of the respondents who received sufficient information support were 22 people (56%). Based on the results of this study, family support in fulfilling Activity Daily Living (ADL) in the elderly must be further enhanced through education from the Village Government with the aim of giving more attention and always providing motivation to families to increase the confidence of the elderly to increase to meet their needs, and to make guidelines for college stude